Adsorptive separations of phytocannabinoids and pesticides in the liquid phase - Cuchiaro, Jamie H., author; Reynolds, Melissa, advisor; Farmer, Delphine, committee member; Chung, Jean, committee member; Reardon, Ken, committee member (Colorado State University. Libraries, 2022)
To view the abstract, please see the full text of the document.
Keywords: HPLC-DAD; MOFs; cannabinoids; pesticides; HPLC-QQQ